A preclinical randomized controlled multi-centre trial of anti-interleukin-17A treatment for acute ischaemic stroke. Issue 2 (23rd March 2023) - Gelderblom, Mathias; Koch, Simon; Strecker, Jan-Kolja; Jørgensen, Carina; Garcia-Bonilla, Lidia; Ludewig, Peter; Schädlich, Ines Sophie; Piepke, Marius; Degenhardt, Karoline; Bernreuther, Christian; Pinnschmidt, Hans; Arumugam, Thiruma V; et al.
Abstract: Multiple consensus statements have called for preclinical randomized controlled trials to improve translation in stroke research. We investigated the efficacy of an interleukin-17A neutralizing antibody in a multi-centre preclinical randomized controlled trial using a murine ischaemia reperfusion stroke model. Twelve-week-old male C57BL/6 mice were subjected to 45 min of transient middle cerebral artery occlusion in four centres. Mice were randomly assigned (1:1) to receive either an anti-interleukin-17A (500 µg) or isotype antibody (500 µg) intravenously 1 h after reperfusion. The primary endpoint was infarct volume measured by magnetic resonance imaging three days after transient middle cerebral artery occlusion. Secondary analysis included mortality, neurological score, neutrophil infiltration and the impact of the gut microbiome on treatment effects. Out of 136 mice, 109 mice were included in the analysis of the primary endpoint. Mixed model analysis revealed that interleukin-17A neutralization significantly reduced infarct sizes (anti-interleukin-17A: 61.77 ± 31.04 mm 3 ; IgG control: 75.66 ± 34.79 mm 3 ; P = 0.01). Secondary outcome measures showed a decrease in mortality (hazard ratio = 3.43, 95% confidence interval = 1.157–10.18; P = 0.04) and neutrophil invasion into ischaemic cortices (anti-interleukin-17A: 7222 ± 6108 cells; IgG control: 28 153 ± 23 206 cells; P < 0.01). There was no difference in Bederson score. The analysis of the gut microbiome showed significant heterogeneity between centres ( R = 0.78, P < 0.001, n = 40). Taken together, neutralization of interleukin-17A in a therapeutic time window resulted in a significant reduction of infarct sizes and mortality compared with isotype control. It suggests interleukin-17A neutralization as a potential therapeutic target in stroke. Abstract : To bridge the gap between experimental research and human clinical trials, Gelderblom et al . investigated the efficacy of interleukin-17A neutralization in a preclinical randomized controlled stroke trial. In the murine stroke model, neutralization of interleukin-17A resulted in a significant reduction of infarct sizes three days after ischaemia. Graphical Abstract: Graphical Abstract